Bibliometric Analysis of Research of Genderlect Communication in 2019-2024 on Google Scholar - Rahardipta, Danar Drestanto (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to analyze the development of research on the topic and title of genderlect by linking emerging concepts through keywords, to provide references for researchers to understand trends in research on genderlect. The method used is a bibliometric analysis of research titled genderlect published between 2019 and 2024, sourced from the Google Scholar database. VOSviewer was applied to conduct the bibliometric analysis of these articles. The results show that 29 studies with the title